PENATAAN FASILITAS WISATA DI KAWASAN PANTAI MANGGROVE SERDANG BEDAGAI SEBAGAI SARANA EDUKASI DAN REKREASI - Ikhsan, Aidil; Marisa, Amy (Universitas Medan Area, 2024)
Mangrove Beach is a beach in the village of Sei Nagalawan, District Serdang Regency, with a different area of 1,000 hectares. Travel from Medan city to Mangrove Beach takes approximately 2 hours by land transportation. It stands as one of the leading tourist attractions in Regency Perbauangan due to its unique and distinctive characteristics that other beaches lack, such as its white sand, often referred to as soursop sand, stretching along the shoreline. Additionally, Mangrove Beach is surrounded by mangrove forests, making it an educational tourism area. There are 13 types of mangroves with potential for development in the Mangrove Beach tourism sector, which necessitates accommodation and other facilities for tourists visiting Sei Nagalawan Village. The methodology employed includes comparative studies, surveys, and literature studies. It is essential to provide complete facilities in the area to attract tourists, offering insight into tropical architecture and considering ecotourism principles by designing a Resort Hotel in the mangrove beach area of Sei Nagalawan village. The provision of complete facilities in the mangrove beach ecotourism area can attract attention. Tropical Architecture, a theme-oriented approach that considers the natural climate and weather while prioritizing thermal comfort, plans and designs effective comfort systems indoors, structures, utilities, and natural ventilation systems, and pays attention to shaping the building facade in harmony with the surrounding environment.